2012
DOI: 10.2174/092986712800609788
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Action of Chelating Agents: Repercussions on the Microorganism Development, Virulence and Pathogenesis

Abstract: Infections caused by resistant microorganisms often fail to respond to conventional therapy, resulting in prolonged illness, increased treatment costs and greater risk of death. Consequently, the development of novel antimicrobial drugs is becoming more demanding every day since the existing drugs either have too many side-effects or they tend to lose effectiveness due to the selection of resistant strains. In view of these facts, a number of new strategies to obstruct vital biological processes of a microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 257 publications
0
57
0
1
Order By: Relevance
“…In fact, this compound has been shown to inhibit the growth of Mycobacterium (20) and Candida (18,19). The mechanism of its antimicrobial properties appears to be related to its ability to selectively disturb essential trace metals required for bacterial metabolism (15,19,21). This compound contains 3 fused benzene rings with o-quinoid moiety and forms strong complexes with transition metal ions at the N-N terminal, with preponderance toward Zn 2+ and to a lesser extent for Fe 2+ , Ca 2+ , Cu 2+ , Co 2+ , and Mn 2+ (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, this compound has been shown to inhibit the growth of Mycobacterium (20) and Candida (18,19). The mechanism of its antimicrobial properties appears to be related to its ability to selectively disturb essential trace metals required for bacterial metabolism (15,19,21). This compound contains 3 fused benzene rings with o-quinoid moiety and forms strong complexes with transition metal ions at the N-N terminal, with preponderance toward Zn 2+ and to a lesser extent for Fe 2+ , Ca 2+ , Cu 2+ , Co 2+ , and Mn 2+ (19).…”
Section: Discussionmentioning
confidence: 99%
“…When MMPs in microbial cells are inhibited, microbial cell homeostasis is disrupted, and growth is retarded (15). MMPs are also present in dentin, and when liberated during resin-based restorative procedures, they could compromise the integrity of the hybrid layer interface and adversely affect the seal provided by resin-based restorative materials (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy and selectivity of azoles depends on the strength of the binding to heme iron as well as the affinity of the N-1 substituent for the CYP51 17 . It has been reported that the presence of iron chelators influences the growth of C. albicans 18,19 . In this respect, thiosemicarbazones iron chelators have been reported as antifungal agents and their activity compared with that of FLC 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Apesar das intrusões serem conhecidas há décadas (Sial, 1976), apenas recentemente têm sido feitas referências sobre efeitos termais provocados nas encaixantes sedimentares (Paiva, 2004;Silveira, 2006;Sousa et al, 2008). Santos (2011), Santos et al (2011Santos et al ( , 2012 e Souza et al (2011) aplicaram o termo buchito a rochas na fácies sanidinito, resultantes de fusão parcial da matriz feldspática de arenitos da Formação Açu. O presente estudo abrange esta formação, principal unidade reservatório da Bacia Potiguar na porção onshore.…”
Section: Introductionunclassified